SAPAAN KEKERABATAN DAN NON KEKERABATANDI BAHASA IHA KABUPATEN FAK-FAK PROVINSI PAPUA BARAT - Hegemur, Jerwin Agustinus; Sinaga, Mangatur; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to describe the forms of kinship greetings in the Iha language in Fak-Fak district, West Papua province and to describe the forms of non-kinship greetings in the Iha language in Fak-Fak district, West Papua. Iha language is the language most often used by people in Fak-fak Regency. Currently, there are many generations who do not know certain regional greeting languages that are used to greet someone according to existing provisions or lineages. This research uses qualitative research with descriptive methods. In this study, researchers obtained data from native speakers of the Iha language who live in Fak-fak Regency, West Papua Province. The results of this research include nineteen greetings of medakinature, namely as follows: (1) Kathagoger (2) Tada Kotnungmbuni, (3) Tada Kehenik, (4) Nia, (5) Nouw, (6) Mandta (7) Nuhu (8) Kuhu (9) Kagah Kandakpoh, (10) Ningmbep Kandakpoh, (11) Kagah Hombi, (12) Ningmbep Hombi, (13) Pamu Nemehar, (14) Pamu Tambuhar, (15) Pamu Kotmambuni, (16) Pamu Kekehing. There are eighteen horizontal greetings, namely as follows: (1) Nen, (2) Nan, (3) Nagha, (4) Nagha Tor, (5) Neniya, (6) Korop , (7) Nakkai, (8) Dwima (9) Ponomi, (10) Pinde, (11) Pedup Nemehar, (12) Pedup Tambhar, (13) Ami Nemehar, (14) Ami Tambha. The non-kinship greeting in the Iha language, Fak-fak Regency, West Papua Province, is a form of expression of respect. Respect fellow citizens, whether based on age,profession, a person's physical nickname, or because of their religious knowledge. The results of this research are expected to be useful for: (1) This research can be used as a source of additional knowledge about greetings (2) This research can be used as additional reference material and reference for researchers regarding greetings (3) This research can be used as learning material for all parties.Key Words: Sociolinguistics, West Papua, Greeting